STATE AND CONSTITUTION IN THE PERSPECTIVE OF PANCASILA: A STUDY OF CONSTITUTIONALISM, THE 1945 CONSTITUTION, AND THE INDONESIAN CONSTITUTIONAL SYSTEM - Bambang Yuniarto; Najwa Nihayah; Lailatul Maulida; Mohammad Dahlan Antasya; Muhammad Yazid Agil; Mohammad Dhafa Abduh Jalal (Adisam Publisher, 2025)
The constitution plays a fundamental role as the supreme law governing the structure and limitations of state power. In the context of Indonesia, the 1945 Constitution (UUD 1945) is the primary foundation, which is inseparable from the philosophical meaning of Pancasila. Pancasila holds a central position as the